2018
DOI: 10.1590/1980-57642018dn12-030013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cognitive functions and central auditory processing in adolescents with non-cholesteatomatous chronic otitis media

Abstract: Auditory deprivation associated with early otitis media with effusion has been considered a risk factor for central auditory processing (CAP), as well as for the development of a number of cognitive functions.Objective:To study the neuropsychological functions of attention, working memory and executive function in adolescents with and without non-cholesteatomatous chronic otitis media (NCCOM) and analyze their interrelationships with the behavioral evaluation of CAP.Methods:Sixty-eight adolescents were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…In various studies, it has been revealed that EOM negatively affects verbal working memory performance (43)(44). There are no studies directly addressing the relationship between EOM and repetition tests.…”
Section: Clinical Significance Of Repetition Testsmentioning
confidence: 99%
“…In various studies, it has been revealed that EOM negatively affects verbal working memory performance (43)(44). There are no studies directly addressing the relationship between EOM and repetition tests.…”
Section: Clinical Significance Of Repetition Testsmentioning
confidence: 99%
“…As funções cognitivas, apresentadas nos artigos [10][11][12][13][14]24 , são explicadas como "constelações de sistemas funcionais complexos que se inter-relacionam com constelações de estruturas cerebrais que lhe servem de substrato" 34 , podendo ser classificadas como percepção, atenção, memória, linguagem e funções executivas, sendo a integração destas funções responsável por grande parte dos comportamentos humanos 33,35 .…”
Section: Funções Cognitivasunclassified